Effect of defect width upon burst capacity of composite repaired pipe - K. E., Leong; Kar Sing, Lim; Ahmad Syahrizan, Sulaiman; Siew Choo, Chin; N., Yahaya (IOP Publishing, 2020)
In recent years, FRP composite wrap repair is the most preferable pipeline rehabilitation system used in the pipeline industry. However, some issues concerning this repair method are not fully understood by the industry. Effect of defect geometries toward the efficiency of composite repaired pipe is one of the issues that concerned by the industry. Pipeline repair design codes and standards have been developed mainly focus on the defect depth and neglect other defect geometries such as defect length and defect width. Previous studies stated that defect geometries especially defect width should not be ignored in evaluating and designing pipe repair system. Therefore, the burst pressure of the composite repaired pipeline subjected to various defect widths was determined through this study in order to evaluate the effect of defect width upon the burst capacity of composite repaired pipeline. Finite element analysis was used to determine the burst capacity of the composite repaired pipe with rectangular shape of defect. There are three different widths were selected with constant defect length and depth. The base model of composite repaired pipe was developed and validated and then modified with the various defect widths in this study. The result shows that burst pressure for three different models vary with a percentage of 12.51% between the maximum burst pressure and minimum burst pressure. The stress contour plot extracted from the finite element analysis revealed that the area of highest stress (557.7MPa) is located around defect region. As the defect is getting wider and subsequently creating a bigger defect area, stress concentration is also getting larger at the defect region. With this, the composite repaired pipe tends to fail at lower pressure when the defect getting wider. Based on the results, the defect width is proven to affect the burst capacity of composite repaired pipe.